Welding consumables : wire electrodes, strip electrodes, wires and rods for arc welding of stainless and heat resisting steels, classification (American Welding Society, 2017)
This specification prescribes the requirements for classification of bare solid stainless steel electrodes (both as wire and strip) for gas metal arc welding, submerged arc welding, and other fusion welding processes. It also includes wire and rods for use in gas tungsten arc welding and plasma arc welding. Classification is based on chemical composition of the filler metal. A guide is appended to the specification as a source of information concerning the classification system employed and the intended use of the stainless steel filler metal. This specification does not include any units other than weight percent. The specification's Annex A makes use of both U.S. Customary Units and the International System of Units (SI). Since these are not equivalent, each system must be used independently of the other.